CD3, CD4 AND CD8 Counts of Asymptomatic and Symptomatic HIV-1 Subjects In Irrua, Edo State, Nigeria - Babatope, I. O.; Esumeh, F. I.; Orhue, P. I.; IYEVHOBU, KENNETH (European Journal of Applied Sciences, 2022)
AIDS is caused by HIV, a pandemic disease and remains a public health concern for many decades. The infection is associated with life threatening opportunistic infections and malignancies. The aim of this study is to determine the CD3, CD4 and CD8 counts of asymptomatic – and symptomatic – HIV-1 subjects in Irrua, Edo State, Nigeria. A total of three hundred and forty four (344) HIV-1 subjects aged between 17-60 years and of both sexes were recruited into this study. The HIV-1 subjects were divided into asymptomatic – and symptomatic – HIV-1 subjects. One hundred and fifty (150) apparently healthy HIV-1 negative subjects served as control. The Cluster of Differentiation (CD) subsets of CD3, CD4 and CD8 counts were enumerated with flow cytometry (Partec cyflow counter). The mean CD3 count of asymptomatic HIV-1 subjects (1388.99 ± 74.98) was not significantly different (P>0.05) compared to control (1463.01 ± 90.34). In contrast, the mean CD3 count of symptomatic HIV-1 subjects (838.63 ± 80.24) was significantly lower (P<0.05) in relation to control (1463.01 ± 90.34). The CD3 count of the study subjects was affected by sex but not by age. The results of the mean CD4 counts of the asymptomatic and symptomatic subjects were 515.45 ± 94.36 and 414.40 ± 77.37 against control (970.62 ± 72.56). The CD4 count was significantly lower (P<0.05) in both asymptomatic and symptomatic groups in relation to control. CD4 count was also affected by sex but not by age. Similarly, the mean CD8 counts of asymptomatic and symptomatic HIV-1 subjects were 689.06 ± 74.56 and 808.30 ± 85.78 respectively against control (556.36 ± 65.04). Statistical comparison showed a progressively significant increase (P<0.05) between asymptomatic and symptomatic groups. CD8 count was significantly increased (P<0.05) in female subjects in comparison to their male counterparts. However, this was more pronounced in symptomatic subjects. Age did not affect the CD8 count of the subjects studied. In conclusion, it has been revealed that the immunological profile of symptomatic HIV-1 subjects was significantly affected compared to asymptomatic and control subjects. It re-emphasizes the need to test subjects and start treatment with antiretroviral drugs early.